Etika Bisnis Islam Pedagang Sapi dan Dampaknya terhadap Kesejahteraan Pedagang di Kecamatan Masbagik Kabupaten Lombok Timur - Ahmad Hulaimi; Sahri Sahri; Moh. Huzaini (Institut Agama Islam Negeri Madura, 2016)
This research aims to determine the Islamic business ethics are implemented and their impact on the welfare of caw traders in the Masbagik districts of East Lombok Region. The method used is descriptive qualitative research with field research type (field research). This research results found that of the study of of Islamic business ethics implemented by cow traders in the Masbagik districts do not yet fully apply the principles of Islamc business ethics, while from a study of the impact of Islamic business ethics towards welfare, not all cow traders in the Masbagik districts of east Lombok region get Islamic welfare because it has not fulfilled the needs dharuriyatnya (prayer and pilgrimage). they had a good life partially. Because it can meet the needs dharuriyatnya. They have said happy, because it has been grateful on rizqi received.